Predictors of visual acuity improvement after phacoemulsification cataract surgery - AlRyalat, Saif Aldeen; Atieh, Duha; AlHabashneh, Ayed; Hassouneh, Mariam; Toukan, Rama; Alawamleh, Renad; Alshammari, Taher; Abu-Ameerh, Mohammed (Frontiers in Medicine, 2022)
Purpose: To assess preoperative predictors of visual outcome after phacoemulsification cataract surgery in Jordan, a Middle Eastern country. Methods: This was a retrospective longitudinal study for adult patients who underwent phacoemulsification cataract surgery from January 2019 to July 2021. For each included patient, we included only first operated eye. We obtained pre-operative ocular history, cataract surgery complication risk based on a predesigned score, visual acuity, best correction, and best corrected visual acuity. We recorded intraoperative complications. We also obtained postoperative best corrected visual acuity and refractive error for correction after 1-3 months. Results: A total of 1370 patients were included in this study, with a mean age of 66.39 (±9.48) years. 48.4% of patients achieved visual acuity >0.8, and 72.7% of patients achieved visual acuity > 0.5. The mean visual acuity improvement after phacoemulsification cataract surgery was 0.33 (95% CI 0.31 to 0.35). On regression model, significant predictors that affected visual acuity improvement included the presence of diabetic retinopathy, glaucoma, and having a complication risk factor (i.e., high risk surgery). Conclusion: Predictors of visual acuity improvement varies between studies, and in this study done in a developing country, we defined predictors of visual acuity improvement. We also provided a new preoperative phacoemulsification cataract surgery complication risk score.